Tinjauan Yuridis Terhadap Penetapan Locus Delicti dalam Kejahatan Dunia Maya (Cyber Crime) Berkaitan Dengan Upaya Pembaharuan Hukum Pidana di Indonesia (Mimbar Keadilan, 2023)
Some of the majority of research highlights the problem of this mode of cybercrime and the need to reform the National Criminal Law to overcome it. What is also a problem is that crimes in cyberspace require a clear locus delicti or a clear place of occurrence because it is one of the requirements for examination by law enforcement agencies. This study aims to review from a juridical perspective the determination of locus delicti in cybercrimes related to efforts to reform criminal law in Indonesia. This study uses a normative juridical approach with a statutory approach. The results of the study concluded that the Criminal Procedure Code does not exclusively regulate how to mention tempus and locus delicti in the indictment. Therefore, the determination of the locus delicti of cybercrime uses the theory of the place where the crime was committed, the theory where the effect was caused, and the theory of the tools used to commit the crime. The problem of cybercrime is not just how to make criminal law policies related to it, but also how to harmonize policies between countries, because the problem of cybercrime has become an international problem and is no longer just a national crime problem.